1986
DOI: 10.3758/bf03211490
|View full text |Cite
|
Sign up to set email alerts
|

On the detection of signals embedded in natural scenes

Abstract: In this paper we consider the processes by which observers can detect and recognize signals embedded in natural scenes and images. Although our results do not strongly support detection processes based strictly upon the cross-correlation (template-matching) of the signal and image luminance profiles, they do support a version of cross-correlation based upon the comparison of their "structural similarities." This latter correlational measure may be separated from the energy component in the cross-correlation fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Then we showed that it is the structural similarity component of the TSSIM that predicts both mean search time and detection probability, while the luminance and contrast similarity components do not correlate with human observer performance. This result agrees with the related observations that the cross-correlation component of the SSIM predicts visual image quality 23 , and that human observers mainly rely on structural features to recognize image content 5,7,8,21,22 . Furthermore, it should be noted that the structural similarity component of the TSSIM is equivalent to a matched filter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Then we showed that it is the structural similarity component of the TSSIM that predicts both mean search time and detection probability, while the luminance and contrast similarity components do not correlate with human observer performance. This result agrees with the related observations that the cross-correlation component of the SSIM predicts visual image quality 23 , and that human observers mainly rely on structural features to recognize image content 5,7,8,21,22 . Furthermore, it should be noted that the structural similarity component of the TSSIM is equivalent to a matched filter.…”
Section: Discussionsupporting
confidence: 92%
“…Visual search experiments have shown that detection performance depends mainly on the energy contrast between a target and its local background, whereas recognition depends mainly on the structural dissimilarity between a target and its surround 5,7 . For complex scenes, the spatial relationships (shape and relative location) of features in an image can have a greater effect on detection than the relative luminance of the features 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It appears that detection performance depends to a large degree on the energy contrast between a target and its local background, whereas recognition depends mainly on the structural dissimilarity between a target and its surround. 52,53 This obscuring effect, which is generally known as clutter, determines human visual search and detection performance to a large extent. For complex scenes, the spatial relationships (shape and relative location) of features in an image can have a greater effect on detection than the relative luminance of the features.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been a number of studies of detection in natural backgrounds (16)(17)(18)(19)(20)(21)(22)(23), they have not directly addressed these questions, and have either tested only a small number of natural stimuli (16,17,19,20), tested natural stimuli with altered statistical properties (21,22), or used experimental paradigms not representative of natural detection tasks (16,(18)(19)(20)23). These latter studies are not as representative of natural tasks, because observers were allowed to directly compare the same image with and without the added target, an advantage that is not normally available under real-world conditions.…”
mentioning
confidence: 99%